Odpowiedź :
5(x-3y)=-7(3y-x)
-3(x+4)+2(3-5y)=0
5x-15y=-21y+7x
-3x-12+6-10y=0
-2x=-6y
x=3y
-3(3y)-12+6-10y=0
-9y-12+6-10y=0
-19y=6
y=-6/19
x=-3*6/19
x=-18/19
a)|2x-1|<3
2x<|4|
x<|2|
x<2
b)|3x+4|≥6
|3x|≥2
x≥|2/3|
funkcji niestety nie mam jak narysować;/
-3(x+4)+2(3-5y)=0
5x-15y=-21y+7x
-3x-12+6-10y=0
-2x=-6y
x=3y
-3(3y)-12+6-10y=0
-9y-12+6-10y=0
-19y=6
y=-6/19
x=-3*6/19
x=-18/19
a)|2x-1|<3
2x<|4|
x<|2|
x<2
b)|3x+4|≥6
|3x|≥2
x≥|2/3|
funkcji niestety nie mam jak narysować;/
Nie mam jak pokazac na osi wiec zaczne od 2 zad. :]
5(x-3y)=-7(3y-x)
-3(x+4)+2(3-5y)=0
5x-15y=-21y+7x
-3x-12+6-10y=0
5x-15y+21y-7x=0
-3x-6-10y=0
-2x+6y=0 /* -3
-3x-6-10y=0 /* 2
6x-18y=0
-6x-12-20y=0
-18y=-12-20y
-18y+20y=-12
2y=-12/:2
y=-6
5x-15y+21y-7x=0
5x-15*(-6) + 21* (-6) - 7x = 0
5x + 90 - 126 - 7x = 0
-2x - 36 = 0
-2x=36 / :(-2)
x= -18
5(x-3y)=-7(3y-x)
-3(x+4)+2(3-5y)=0
5x-15y=-21y+7x
-3x-12+6-10y=0
5x-15y+21y-7x=0
-3x-6-10y=0
-2x+6y=0 /* -3
-3x-6-10y=0 /* 2
6x-18y=0
-6x-12-20y=0
-18y=-12-20y
-18y+20y=-12
2y=-12/:2
y=-6
5x-15y+21y-7x=0
5x-15*(-6) + 21* (-6) - 7x = 0
5x + 90 - 126 - 7x = 0
-2x - 36 = 0
-2x=36 / :(-2)
x= -18